Endoscopic ultrasound‐guided drainage of a mediastinal abscess related to endobronchial ultrasound‐guided transbronchial needle aspiration. Issue 5 (28th April 2022) - Ikeda, Yuki; Ono, Michihiro; Maeda, Masahiro
Abstract : Watch a video of this article.